(untitled) (Altre Modernità, 2024)
In the third-world constellation of Italian anti-colonialism, Milan certainly occupies a central place for the political reworking, cultural reception and editorial dissemination of authors and literature from the South of the World, especially from the late 1950s onwards. In the context of the cultural solidarity actions undertaken in Italy towards African liberation movements fighting against Portuguese colonialism (1961-1974), the case of the translation and dissemination of the poetic work of Agostinho Neto by Joyce Lussu, a former partisan and anti-colonialist militant, seems paradigmatic of an entire Milanese and Italian season of soutien to the cause of peoples fighting for their independence.